Gender transformative socio-technical innovation bundling scaling workshop report - Makueni County, Kenya - Lutomia, Cosmas Kweyu; Ouya, Fredrick Ochieng'; Njiru, Emerita; Mutua, Miriam; Waswa, Boaz; Ketema, Dessalegn; Nchanji, Eileen (2025)
This report documents a two-day Gender-Transformative Socio-technical Innovations Bundling (GTSTIBs) scaling workshop held in Wote, Makueni (15–16 Sept 2025). Stakeholders, county officials, researchers, farmers, NGOs, and private sector, reviewed pilot evidence from learning labs that tested GTSTIBS in Kenya and co-designed a county roadmap. Key takeaways: GTSTIBs improved productivity, dietary diversity, and women’s empowerment. Scaling needs extension capacity, social-innovation integration, private-sector engagement, policy anchoring, and budget support. Outputs included an agreed roadmap, program integration commitments, and strengthened partnerships for sustained, equitable countywide adoption.